Counterintuitive migration patterns by Atlantic salmon Salmo salar smolts in a large lake. Issue 1 (30th August 2018) - Honkanen, Hannele M.; Rodger, Jessica R.; Stephen, Alastair; Adams, Keith; Freeman, James; Adams, Colin E.
Abstract : What little is known about the seaward migration of Salmo salar smolt migration through standing waters indicates that it is both slow and results in high mortality rates, compared with riverine migration. This may be partly because smolts in lakes need to swim more actively and require more complex directional cues than they do in rivers. In this telemetry study of smolt migration through Loch Lomond, S. salar smolts made repeated movements in directions away from the outflowing river, which considerably increased migration time.